Pharmacological Inhibition and Genetic Knockdown of BCL9 Modulate the Cellular Landscape of Cancer-Associated Fibroblasts in the Tumor-Immune Microenvironment of Colorectal Cancer - Yang, Mengxuan; Wei, Zhuang; Feng, Mei; Zhu, Yuanyuan; Chen, Yong; Zhu, Di (Frontiers in Oncology, 2021)
Cancer-associated fibroblasts (CAFs) exert a key role in cancer progression and liver metastasis. They are activated in the tumor microenvironment (TME), but their prometastatic mechanisms are not defined. CAFs are abundant in colorectal cancer (CRC). However, it is not clear whether they are raised from local tissue-resident fibroblasts or pericryptal fibroblasts and distant fibroblast precursors, and whether they may stimulate metastasis-promoting communication. B-cell lymphoma 9/B-cell lymphoma 9-like (BCL9/BCL9L) is the key transcription cofactor of β-catenin. We studied the TME of CRC with single-cell sequencing and consequently found that Bcl9 depletion caused a pro-tumor effect of CAFs, while inhibition of abnormal activation of Wnt/β-catenin signal through Bcl9 depletion benefited T-cell–mediated antitumor immune responses. We also identified and evaluated four types of CAFs in CRC with liver metastasis. In summary, we demonstrate cell type landscape and transcription difference upon BCL9 suppression in CAFs, as well as how CAF affects cancer associated immune surveillance by inhibition of Wnt signaling. Targeting the Wnt signaling pathway via modulating CAF may be a potential therapeutic approach.